(untitled) (Swiss Medical Weekly, 2016)
AIMS OF THE STUDY: Although solar overexposure during childhood and adolescence increases the risk of melanoma, determinants of sunburn and sun protective behaviours of Swiss children have scarcely been explored.We investigated sunburn occurrence and sun protective behaviours of schoolchildren in western Switzerland, the region with the highest incidence of melanoma in Europe. MATERIAL AND METHODS: Self-reported questionnaires were administered during regular classes to pupils in 5th (primary school, n = 431), 8th and 11th grades (secondary school, n = 837) in the 18 public schools of La Chaux-de-Fonds. Descriptive statistics and multivariate logistic regression analyses were performed to assess predictors of sunburns and of three sun protective behaviours (sunscreen, shade, wear of covering clothes). RESULTS: Response rate was 91%. Sunburn prevalence over the preceding year was high (60% at least one sunburn, 30% at least two, 43% at least one severe sunburn). Younger age, fair skin, regular sunscreen use, higher sun-related knowledge and preference for a tanned skin were predictors of sunburn. Sunscreen was the most used protective measure (69%), followed by seeking shade (33%) and wearing long-sleeved shirts (32%). Decline in all protective measures was observed in older pupils and those with pro-tan attitudes. The wear of covering clothes was significantly associated with sunscreen use and seeking shade. Parental encouragement favoured sunscreen use and wearing of protective clothes. CONCLUSIONS: Sunscreen use as a last protective barrier against ultraviolet radiation should be better emphasised in prevention campaigns targeting children and adolescents. Multi-faceted interventions, including role models, parents and peers should help to improve children’s sun protective behaviours.